Lessons from Korea to Africa : leaders, politics and developmental states - Mah, L. (WP CESA, 2011)
A recent series of studies have been dealing with the dynamics behind the building of developmental states in Africa. This working paper is a contribution for that debate by looking at the experience of the Korean developmental state and the lessons that Africa can learn from this Asian country’s experience seen as an outstanding model of economic development. Despite poor resource endowment and a large population, a colonial legacy, the devastation following a civil war, persistent political instability, and the lingering military confrontation with her northern neighbour, Korea’s role in the international economic system has rapidly increased in importance since the 1960s. For nearly five decades, Korea has achieved a remarkable economic performance that transformed the country from a typical case of a developing nation trapped in a “vicious circle of underdevelopment”, into one of the largest economies in the late 1990s. Beneath the economic success lied a system of “socialisation of private risk”, a particular mode of organising the market, as the “visible hand” of a strong, bureaucratic and developmental state were able to accelerate the pace of economic growth by identifying strategic industrial sectors, making discretionary allocation of resources to those sectors, and minimising the collective action dilemmas pervasive in most developing countries. But the Korean state, as any other state, is a political realm that encompasses distinct, contending and at times colliding actors. In fact, the Korean developmental state provides us clues about the role that leadership play and what stands at the “heart of a politics of economic growth”. Policy choices and implementation rest on the strategies designed by the rulers to boost their political legitimacy, to strengthen their power, and to guarantee regime survival. Strategies are not only a product of institutional opportunities and constraints, but also of history, context, coalition politics and ideological templates involving the actors at the time of action. This paper will discuss the role played by President Park Chung-Hee (1961-1979) in building a bureaucratic-developmental state and what African countries can learn from these leadership experiences in terms of its own development path.